Pollen morphology of four endemic species of Pedicularis L. from alpine zone of the Deosai Plateau, Himalayan range - Bano, Abida; Ahmad, Mushtaq; Khan, Mir Ajab; Zafar, Muhammad; Sultana, Shazia; Ullah, Zahid (Bangladesh Journal of Plant Taxonomy, 2012)
The pollen morphology with special reference to exine sculpturing of four species of the genus Pedicularis L. has been examined by light and scanning electron microscope. Comparative pollen analysis was made based on the type of pollen, shape in polar and equatorial views, P/E ratio, exine thickness and sculpturing of pollen. In this study, two types of pollen aperture configuration known in the genus were observed i.e., trisyncolpate and bi-syncolpate. Pollen grains with microscabrate ornamentation were found in bi-syncolpate pollen for the first time. Pollen fertility estimation ranged from 87-95%, which shows that pollen flora of selected species is well established in Alpine zone. DOI: http://dx.doi.org/10.3329/bjpt.v19i1.10935 Bangladesh J. Plant Taxon. 19(1): 1-5, 2012 (June)